Increase in antioxidant and antihypertensive peptides from Argentinean wines by Oenococcus oeni - Aredes Fernández, Pedro Adrián (2013)
Cells from an exponential Oenococcus oeni m1 culture in a grape juice medium were inoculated into a synthetic wine medium (SW) supplemented with a protein and polypeptide fraction (PPF) of high molecular weight (higher than 12,400 Da) obtained from four varietals of Cafayate Argentinean wines. O. oeni maintains viability after 48 h incubation time and enables the increase in extracellular proteolytic activity and the release of low molecular weight peptides by 1.067, 0.397, 0.915 and 0.705 mg N/L in the respective SW supplemented with PPF from Cabernet Sauvignon, Malbec, Tannat and Torrontés wine varietals. After 48 h incubation time, concomitantly with peptide release, an increase in antioxidant and antihypertensive activities was detected in all studied media. The highest increase was detected in the presence of PPF from Cabernet and Tannat wine varietals. Maximum increase in antioxidant activity (366.1 μmol FeSO4/L in the case of ferric reducing antioxidant power and 8.9% in 2,2-diphenyl-1-picrylhydrazyl radical scavenging) was produced by the peptides released from PPF of Cabernet Sauvignon wine. The peptides released from PPF Tannat wine varietal caused the highest increase in antihypertensive activity (56.2% in angiotensin I-converting enzyme inhibitory activity). Oenococcus oeni m1 would provide additional benefits to wine such as an increase in bioactive peptides with multifunctional beneficial activities.